Loin pain and a normal CT KUB: what to do?. Issue 2 (29th April 2020) - Walker, Nicholas Faure; Kirby, Roger
Abstract : Persistent loin pain and a normal CT KUB can present a significant challenge to urologists. A thorough history and examination may well identify the underlying cause. Further investigations may be indicated, but the benefits of more invasive testing and further radiation exposure must be carefully balanced against the risks.